The Asymmetric Impact of Monetary Policy and Banking Credits on Business Cycles in Iran: A Threshold VAR Approach - Ahmad Jafari Samimi; Mohammad Ali Ehsani; amirmansour tehranchian; Zeinab Gholami (مدلسازی اقتصادسنجی, 2017)
This paper using a threshold vector autoregressive examines the asymmetric impacts of monetary policy and banking credits on business cycles in Iran. In this paper the output gap is defined as transmission variable between two regimes and the Hodric-Prescott is estimated and its stationary is confirmed by Dickey-Fuller test. Using the likelihood ratio test the nonlinearity of the model is tested and using grid search method the threshold variable is determined. Base on threshold value (-0.000922) two regimes including upper and low regime are considered. Using R software the threshold vector autoregressive model is estimated and generalized impulse response function are extracted. Results indicate that the impact of monetary policy and banking credits on economic activity in low and upper regimes is completely different and depending on business cycle condition, In other words the paper findings support the asymmetric impact of monetary policy and banking credits in Iran.